Monte Carlo Calculation of Relative Dose Distribution and Dosimetry Parameters for an 192Ir Source in a Water Phantom Using MCNP4C - H. Arabshahi3*, A. Binesh2, A.A. Mowlavi1, and (Journal of Experimental Sciences, 2010)
Abstract The dose distribution has been calculated around a high dose rate 192Ir source located in the center of 30 cm ×30 cm ×30 cm water phantom cube using MCNP code by Monte Carlo method. The percentage depth dose (PDD) variation along the different axis parallel and perpendicular the source are calculated. Then, the isodose curves for 50%, 25%, 10% and 1% PDD have been presented. The Monte Carlo results are in fair agreement with the experiment dosimetry by Gafchromic Rtqa film. Finally, dosimetry parameters of TG-43 protocol have been determined and compared with the results of others. <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Keywords: Brachytherapy, Dose distribution, Monte Carlo method, MCNP code, Anisotropy function, Gafchromic Rtqa film Please Cite This Article As: A. Binesh, A.A. Mowlavi, and H. Arabshahi. 2010. Monte Carlo Calculation of Relative Dose Distribution and Dosimetry Parameters for an 192Ir Source in a Water Phantom Using MCNP4C. J. Exp. Sci. 1(4):32-36.